Investments - Bodie, Zvi (McGraw-Hill Education series in finance, insurance, and real estate., 2018)
"The integrated solutions for Bodie, Kane, and Marcus' Investments set the standard for graduate/MBA investments textbooks. The unifying theme is that security markets are nearly efficient, meaning that most securities are priced appropriately given their risk and return attributes. The content places greater emphasis on asset allocation and offers a much broader and deeper treatment of futures, options, and other derivative security markets than most investment texts. Connect is the only integrated learning system that empowers students by continuously adapting to deliver precisely what they need, when they need it, and how they need it, so that your class time is more engaging and effective." --